Extremely compact EBG‐backed antenna for smartwatch applications in medical body area network. Issue 7 (20th March 2019) - Rano, Dinesh; Hashmi, Mohammad
Abstract : This paper presents design of a compact interdigital electromagnetic band gap unit cell (IDE) for wearable applications in the medical body area network (MBAN) band. The uniqueness of the proposed cell is in its ability to achieve lower resonant frequency in spite of very compact size of 14.3 mm × 14.5 mm. The cell has adjacent fingers connected in such a way that the net inductance contributed by the metallic strips increases and this aids in the reduction of resonant frequency. An equivalent lumped circuit model supports the analysis of the proposed cell. The evaluation of the developed model is assessed by comparing the reflection phase response obtained from the circuit model and full wave analysis. The proposed design, even though slightly asymmetric, possess polarisation stability and this has been validated using the reflection phase parameter for a plane wave polarised along x ‐and y ‐axes. Subsequently, a reflector consisting of 2 × 2 IDE‐unit cell to be integrated with monopole antenna of overall size 36 mm × 38 mm × 3.12 mm is designed. The design exhibits a very good agreement between the experimental and the simulated results whereby it is able to provide gain and efficiency of 5.3 dB and 85% respectively at the MBAN frequency.